SCHOOL MANAGEMENT IN THE FRAMEWORK OF ACADEMIC DEVELOPMENT IN COLOMBIA - Deisy Johanna Balaguera Restrepo; Gerson Enrique Silva Labarca (LÍNEA IMAGINARIA, 2025)
School management within the framework of academic development in Colombia is a strategic and participatory process that seeks to improve the quality of education, promote equity, and ensure compliance with the educational standards established by national policies. In this context, school management is conceived as a key element for strengthening educational institutions, optimizing resources, and promoting environments conducive to learning. More broadly, this article aims to analyze how school management is carried out within the framework of academic development in Colombia. As an essay, it is specified as possible outcomes. It is important to note that academic development in Colombia is also linked to the implementation of programs and strategies that promote pedagogical innovation, the use of educational technologies, and student-centered methodologies. Efficient school management facilitates the incorporation of these elements, ensuring that all stakeholders work together to raise learning levels and reduce existing inequalities in different regions of the country.